Compression power requirements for Oxy-fuel CO2 streams in CCS - Daud, Nor Khonisah; Martynov, Sergey; Mahgerefteh, Haroun; Nasuha, Norhaslinda (IOP Publishing, 2019)
CO2 compression systems are commonly designed assuming negligible amount of impurities in CO2 fluid, it is of practical interest to evaluate the impact of impurities in oxy-fuel streams on the compression power requirements. Compared to more traditional postcombustion and pre-combustion capture methods, oxy-fuel technology produces a CO2 stream with relatively high concentration of impurities that may require partial or a high level of removal and whose presence can be expected to increase the costs of CO2 compression. Four types of compression technologies employed include four-stage compressor with 4 intercoolers, single-stage supersonic shockwave compressor, three-stage compressor combined with subcritical liquefaction and pumping and three-stage compressor combined with supercritical liquefaction and pumping. The study depicts that decrement of the impurities content from 15 to 0.7%v/v in the CO2 streams reduced the total compression power in the compression system. The study also concludes that three-stage compressor combined with subcritical liquefaction and pumping can potentially offer higher efficiency than four-stage compressor with 4 intercoolers for almost pure CO2 streams. In the case of raw oxy-fuel mixture, that carries relatively large amount of impurities, subcritical liquefaction proved to be less feasible, while supercritical liquefaction efficiency is only marginally lower than that in the four-stage compressor with 4 intercoolers.